The Influence Of Microeconomic Factors And Macroeconomic Factors On Stock Price Volatility In KOMPAS 100 Index Companies Listed On The Indonesia Stock Exchange For The Period 2019-2022 - Putri, Abel Lina; Paramita, R.A. Sista (Journal of Business and Management Review, 2024)
Research Aims: This study aims to determine the effect of dividend payout ratio, firm size, leverage, earning volatility, exchange rate, inflation, and interest rate on stock price volatility in KOMPAS 100 index companies listed on the Indonesia Stock Exchange for the period 2019-2022 Design/methodology/approach: The type of data used is quantitative data sourced from secondary data. The population in this study is the KOMPAS 100 index company listed on the Indonesia Stock Exchange for the 2019-2022 period. The technique used in this sampling is purposive sampling and 33 companies were obtained as samples in this study. The data was analyzed using multiple linear regression and calculated with SPSS Version 25 software. Research Findings: The results showed that earning volatility, inflation, and interest rates have a significant positive effect on stock price volatility. Meanwhile, firm size and exchange rate have a significant negative effect on stock price volatility. However, dividend policy proxied by the dividend payout ratio and leverage proxied by debt to equity ratio have no significant effect on stock price volatility. Therefore, companies included in the KOMPAS 100 index should optimize total assets to increase profitability, and also stabilize profits, cost efficiency both operational and non-operational and assess financial risk to minimize investment risk and to overcome the impact macroeconomic  conditions,  so that companies are able to control the level of stock price volatility.  Theoretical Contribution/Originality : This study provides new insights into how the influence of microeconomic factors explained by dividend payout ratio, firm size, leverage, and earning volatility, as well as macroeconomic factors explained by exchange rate, inflation, and interest rate on stock price volatility.  Keywords: Dividend payout ratio; Firm size; Leverage; Earning volatility; Exchange rate; Inflation ;Interest rate